HandMATE: Advancing Accessible Hand Rehabilitation for Persons With Stroke - Matteo Pergami-Peries; Megan Grainger; Peter S. Lum (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Stroke is a leading cause of disability worldwide. HandMATE (Hand Movement Assisting Therapy Exoskeleton) addresses accessibility and cost related challenges associated with clinic-based stroke rehabilitation by providing a home-based robotic solution for hand rehabilitation. This study involved 14 chronic stroke patients (10 female, 4 male, average Fugl-Meyer Assessment (FMA) score of 24). Each took home and used a customized HandMATE over a 4-month period. During the first month (Phase 1), subjects had weekly clinic visits for troubleshooting problems and device improvements. During the next 3 months (Phase 2), subjects continued to use the device without weekly clinic visits. Assessments included the FMA, Action Research Arm Test (ARAT), motion capture, and device usage data. There were statistically significant improvements compared to baseline in clinical scores and finger range of motion at the end of Phase 1 (FMA: $Δ \bar {x} = +3.69$ , $σ =3.54$ , p =0.0027; ARAT: $Δ {\bar {\text {x}}} = +1.85$ , $σ =2.79$ , p =0.0346), and substantial but not significant improvements at the end of Phase 2 (FMA: $Δ {\bar {x}} = +2.67$ , $σ =4.15$ , p =0.0903; ARAT: $Δ {\bar {\text {x}}} = +2.67$ , $σ =4.15$ , p =0.0903). Qualitative feedback indicated high user satisfaction, but highlighted areas for improvement. Usage declined during Phase 2, suggesting the need for engagement strategies. Despite these challenges, the study highlights HandMATE’s potential to enhance recovery outcomes by addressing barriers to traditional rehabilitation settings. Future iterations will focus on increasing durability, portability, and user engagement, paving the way for broader adoption of home-based robotic rehabilitation devices.